Some issues of intercultural sensitivity and values - Kriaučiūnienė, Roma (Verbum, 2015)
Intercultural sensitivity, being defined as an attitude reflecting the degree of willingness to interact with people from different cultures, is considered to be crucial to promote dialogue between cultures and social cohesion in today’s diverse and globalised world. Based on the qualitative research carried out at Vilnius University, the article presents the findings of students’ viewpoints on the place of values in decision making process in an intercultural workplace environment. The respondents’ answers revealed their emotional empathy as well as readiness to solve conflicting situations in a constructive way, in the form of dialogue and negotiations, with reference to values as the criteria of evaluation. A conclusion is made that the demonstrated level of students’ emotional empathy and their reliance on values could have a positive impact on their intercultural sensitivity.